Robust nonlinear control of a buoyancy-driven airship system using backstepping integral sliding mode control - Maziyah, Mat Noh; Mohd Rizal, Arshad; Rosmiwati, Mohd Mokhtar (Springer Science and Business Media Deutschland GmbH, 2022)
This paper presents the development of nonlinear robust control based on backstepping and sliding mode control system to control a longitudinal plane of a new concept of airship. Nature of autonomous airship is non-rigid body, very nonlinear and therefore control strategy can be used to accommodate the nonlinearities in the airship model. The performance of the proposed controller is simulated using MATLAB/Simulink software which tested for nominal system, system with external disturbance and system with parameter variation to evaluate its robustness against external disturbance and parameter variations. The controller is designed for the gliding path from 10° downward to 10° upward. The performance of proposed controller is compared against the performance of backstepping sliding mode control and integral sliding mode control in terms of chattering reduction and steady state error. The simulation results have shown that the proposed controller has improved the output tracking performance around 25% better as compared to lowest performance of integral sliding mode and the undesired chattering in control input and sliding surface has been reduced almost 100%.